Image Re-colourisation In Understanding the Red-Green Colour Blindness - Wan Ayub, Wan Ahmad Rahimi; Mohamad, Mazita (Evolution in Electrical and Electronic Engineering, 2022)
The main objective of this research is to develop a re-colourisation image using MATLAB to mimic a type of Red-Green colour blindness, i.e Deuteranopia. Deuteranopia is one type of colour-deficient disease (CVD). People with deuteranopia cannot identify the difference between red and green colour, hence it is also known as red-green colour blindness. This paper focuses on the image processing technique to recolourisation of the image from red, green, yellow, and beige. The methodology involves image acquisition, image pre-processing, and detection of colour. There are two methods used such as RGB thresholding masking and recolour method. This project uses an RGB threshold for masking and detection of colour. recolour images are required to substitute colour from green or red to yellow or beige. After the recolour method was applied, compared processed images in this project with reference processed images to show a trend with the recolour method. The image quality after decolourisation showed very little degradation with the BRISQUE score difference between pre-processing image and the post-processing image of 1.067 and 2.4068 for the green and red images, respectively. In conclusion, the objective of evaluating the image’s effectiveness in increasing public awareness of persons who suffer from colour vision deficiency should be achieved.